The effect of gender diversity on firm performance in Indonesia - Keyi Sylvia Tania; Hesniati Hesniati (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This study investigates the relationships between gender diversity in the board of directors and firm performance. It also uses several control variables: education, age, tenure, board size, board meeting, firm size, firm age, and leverage. We examine the relationship between variables with several methods, such as descriptive statistic methods, correlation tests, t-tests, and hypothesis testing on 29 LQ45 companies from 2016-2020. Our finding shows that gender diversity on the board of directors significantly negatively impacts firm performance. Despite the negative research results, we still recommend that companies increase gender diversity on the board of directors because many studies state a positive relationship between gender diversity on the board of directors and firm performance. In addition, the small number of women on the board of directors is less capable of positively affecting company performance, whereas, in this study, the number of women in each company each year is relatively small. The limitations of this study are that the number of years studied is only five years and the measurement of gender diversity only uses one proxy.